Cardiac computed tomography for therapy targeting in surgical repair of anteroapical left ventricular aneurysms: assessment of aneurysm volume and of anticipated residual left ventricular volume. (8th February 2021) - Solowjowa, N; Nemchyna, O; Hrytsyna, Y; Meyer, A; Pasic, M; Falk, V; Knosalla, CH
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Surgical ventricular repair (SVR) is an established treatment option in patients with heart failure (HF) due to left ventricular (LV) aneurysms, whereby LV volume reduction is the principal therapeutic target. Precise planning therefore is essential for postoperative improvement of HF symptoms. Purpose: In this study we evaluated the potential of cardiac computed tomography (CCT) to estimate the aneurysm volume and to predict the achievable residual LV volume. Methods:  205 patients (11/2005-01/2016, m:w = 151:54, median 63.4 years; mean NYHA class 3.03) with anteroapical LV aneurysm underwent SVR combined with coronary artery bypass grafting (77%), mitral valve repair/replacement (19%), and LV thrombectomy (19%). CCT was performed before and 7 days after surgery. Volumetric assessment was made using dedicated software (syngo.via Cardiac Function, Siemens AG).  Preoperative CCT data of 48 consecutive patients were analyzed and then matched with effectively achieved postoperative volumes. To separate the aneurysm volume in the systole and diastole a plane determined by three landmarks on borders of scared to intact LV myocardium (antero-septal, lateral and inferior) was used. In this way ensued the retrospective estimation of the aneurysm volume (AnV/AnVI) and anticipated LV end diastolic and end systolic volume (LVEDVI, LVESVI). Results: Mean diastolic and systolic estimated AnV were 92 ± 56.6 ml and 83.5 ± 61.6 ml respectively. Relation of AnV to LVEDV and to LVESV was 29.2% and 38.2%, correspondingly. There was significant correlation between anticipated and effectively achieved LVEDV and LVESV (r = 0.87 and r = 0.88, respectively, p < 0.0001), and their indexed values (r = 0.83 and r = 0.83, respectively, p < 0.0001). Anticipated LVEDVI was only 10.3 ± 22.5 ml/m2 greater than achieved LVEDVI (p = 0.003), and anticipated LVESVI was only 2.4 ± 20.3 ml/m2 greater than achieved LVESVI (p = 0.433). Conclusions: Estimation of aneurysm volume and anticipated postoperative LV volume allows to predict if the therapeutic targets can be successfully achieved in individual patients. Based on the CCT assessment we propose an approach for surgical planning in anterior LV aneurysms.